Mulheres negras que amam mulheres: travessias e deslocamentos na produção de subjetividades - Souza, Juliane Campos de (2021)
This dissertation aims to map some processes of subjectivation of black women who love women. It also problematizes these processes based on the affirmation of other invented ways of existing in everyday life. It makes use of cartography and Conceição Evaristo's notion of escrevivência: an embodied and committed writing, whose starting point are the –singular and collective– intensive memories and experiences. It is a crossing that encounters the prison in the effects of coloniality – fragments of a wound-body – displacing it into new modes of existence – traces of the creation of a cross-body. The crossing requires alliances with ancestral sensibilities and knowledges, and with authors such as Grada Kilomba, bell hooks, Glória Anzaldúa, Jota Mombaça. The writing is, therefore, part of an experience of embodiment of life